Fields of Danger: Communicating Agricultural Safety and Health Information - Judy Barnes Oskam (Journal of Applied Communications, 1992)
It happened January 11, 1992. Eighteen-year-old John Thompson was seriously injured in an agricultural machinery accident on the family's North Dakota farm.